Africa south of the Sahara food security portal - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
IFPRI's portal dedicated to Africa south of the Sahara focuses on food and nutrition security for the whole region. The objective of the portal is to provide a set of indicators on food and nutrition security and early warning mechanisms as well as opportunities for dialogue among policymakers, researchers, the private sector and others seeking to increase the resilience of the world’s poor to possible food-related crises, including price and climate shocks.